Diurnal variations of hormonal secretion, alertness and cognition in extreme chronotypes under different lighting conditions - Maierova, L; Borisuit, A; Scartezzini, J-L; Jaeggi, S M; Schmidt, C; Münch, M (Scientific reports, 2016)
Circadian rhythms in physiology and behavior are modulated by external factors such as light or temperature. We studied whether self-selected office lighting during the habitual waking period had a different impact on alertness, cognitive performance and hormonal secretion in extreme morning and evening chronotypes (N = 32), whose preferred bed- and wake-up times differed by several hours. The self-selected lighting condition was compared with constant bright light and a control condition in dim light. Saliva samples for hormonal analyses, subjective ratings of alertness, wellbeing, visual comfort and cognitive performance were regularly collected. Between the self-selected and the bright, but not the dim lighting condition, the onset of melatonin secretion in the evening (as marker for circadian phase) was significantly different for both chronotypes. Morning chronotypes reported a faster increase in sleepiness during the day than evening chronotypes, which was associated with higher cortisol secretion. Wellbeing, mood and performance in more difficult cognitive tasks were better in bright and self-selected lighting than in dim light for both chronotypes, whereas visual comfort was best in the self-selected lighting. To conclude, self-selection of lighting at work might positively influence biological and cognitive functions, and allow for inter-individual differences.
Keywords: dospělí; hydrokortison; melatonin; Hormones; sliny; Attention; Humans; Young Adult; Melatonin; mladý dospělý; Lighting; Hydrocortisone; cirkadiánní rytmus; kognice; mužské pohlaví; pozornost; afekt; spánek; Adult; osvětlení; Affect; Adolescent; hormony; ženské pohlaví; bdění; Wakefulness; Cognition; lidé; mladiství; Sleep; Male; Saliva; Circadian Rhythm; Female